Occurrence of substituted diphenylamine antioxidants and benzotriazole UV stabilizers in Arctic seabirds and seals - Lu, Zhe; De Silva, Amila O.; Provencher, Jennifer F.; Mallory, Mark L.; Kirk, Jane L.; Houde, Magali; Stewart, Connor; Braune, Birgit M.; Avery-Gomm, Stephanie; Muir, Derek C. G. (Science of The Total Environment, 2019)
Substituted diphenylamine antioxidants (SDPAs) and benzotriazole UV stabilizers (BZT-UVs) are contaminants of emerging environmental concern. However, little is known about the occurrence of these contaminants in the Arctic. In this study, we investigated the levels of 11 SDPAs and 6 BZT-UVs in livers and eggs of two seabird species, the black-legged kittiwake (Rissa tridactyla) and northern fulmar (Fulmarus glacialis), as well as the liver of ringed seals (Pusa hispida) from Canadian high- and sub-Arctic sites. The concentrations of ΣSDPAs in seabird livers (median 336 pg g, wet weight (ww)) were significantly higher than the eggs (median 24 pg g, ww) and the seal livers (median 38 pg g, ww), suggesting liver was a primary tissue of SDPA accumulation in seabirds and that seabirds were at greater risk of exposure to SDPAs than marine mammals in the Arctic. The predominant SDPA was monostyryl octyl-diphenylamine and this compound was detected in every seabird and seal sample, indicating the widespread distribution of this contaminant in Arctic food webs. Unlike SDPAs, the detection rate and concentrations of BZT-UVs in seals were higher than in seabirds. The compound 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (UV329) or its isomer 2-(2H-benzotriazol-2-yl)-4-(tert-butyl)-6-(sec-butyl) phenol (UV350) was the predominant BZT-UVs in seals, with the concentrations of ΣBZT-UVs between